The investigation of Helicobacter pylori in the dental biofilm and saliva samples of children with dyspeptic complaints - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (BMC, 2017)
Background: The oral cavity can be an extra-gastric reservoir for Helicobacter pylori (H. pylori). This can play a role in the pathogenesis of halitosis, glossitis, recurrent aphthous stomatitis, and dental caries. The present study was conducted to detect the presence of H. pylori within the dental biofilm and in saliva samples collected from children suffering from dyspepsia and children without any gastrointestinal complaints. Associations with gastric infection, halitosis, and some oral parameters were also evaluated. Methods: Seventy children (aged between 5-16) with dyspepsia were selected for the study group and control group composed of 30 healthy children without dyspepsia were also included in the study. After detailed oral and clinical examinations for oral parameters, saliva, and supragingival dental biofilm samples were collected for 16S rRNA and 23S rRNA genes detection by real-time polymerase chain reaction (RT-PCR). The presence of gastric H. pylori was evaluated in endoscopic biopsy specimens histopathologically. Halitosis was evaluated by benzoylDL-arginine-naphthylamid (BANA) test. Salivary S. mutans and Lactobacilli sp. counts were also carried out by commercial kits. Results: H. pylori was histopathologically detected amongst 83% of the children with the dyspeptic condition. The detection rate of this bacteria in dental biofilm and saliva samples and halitosis were found relatively higher in the dyspeptic children rather than the control group (p < 0.01). Halitosis was not significantly different between dyspeptic children and those detected with H. pylori (p > 0.05). In the gastric H. pylori positive group with dyspepsia, DMFT/ S and dmft/ s numbers and plaque indices were found higher than the control group (p < 0.01). Only plaque indices of gastric H. pylori negative group with dyspepsia were found higher than the control group (p < 0.01). S. mutans and Lactobacilli sp. counts were not significantly different between gastric H. pylori positive and negative groups (p > 0.05). Comparing to those with negative for both genes, in children whose dental biofilm and saliva samples were positive for both 16S rRNA and 23S rRNA genes, significantly higher results for halitosis, and DMFS numbers and significantly lower results for dmfs numbers and pH values were found (p < 0.01). Conclusions: Helicobacter pylori can occur in the oral cavity aside and independently from the stomach. However, the high number of bacteria in the oral cavities of children with gastric H. pylori, an association between the presence of H. pylori and halitosis, DMFS, and pH were found.
Keywords: Helicobacter pylori; RT-PCR; Dental biofilm; Saliva; Halitosis; POLYMERASE-CHAIN-REACTION; ORAL-CAVITY; CHRONIC PERIODONTITIS; RISK-FACTORS; PLAQUE; INFECTION; DNA; TRANSMISSION; ERADICATION; PREVALENCE